Práticas informacionais e velhice: análise do fluxo informacional dentro de asilo na cidade de Cuité e sua contribuição para inclusão da pessoa idosa. - Gomes, Jesiel Ferreira (2011)
Back scientific scrutiny to a social stratum, and it inserts that do research and seek his understanding is one pillar of fundamental importance for the social sciences. More importantly, when this layer is made up of people shut out from society, separated and isolated from others, such as the institutionalized elderly as a whole. Old age has two strands that daily distance themselves at opposite poles, where on the one hand there are the elderly with economic potential and embedded in a social environment in which they consume and participate actively in social and family decisions. On the other hand, a number of people in forgotten places called asylums. Often, these people do not have the financial resources, nor health, to have activity in the society that surrounds him. With the latter, the work presented here is presented with the purpose of responding to the flux of information, drawn from the information practices may contribute to the inclusion of the institutionalized elderly in the town of Cuité - PB, society and contribute to their full citizenship . For the purpose it was used as a descriptive research methodology in order to serve as a basis for future studies and actions that may be developed. With the data obtained, it is important to realize that indeed there are no conditions for most of the institutionalized elderly, to participate fully in the information flow of asylum, due to factors such as special needs, culture in which it is inserted, way of life limited by structural conditions in which he lived, lack of economic resources and lack of interest in life itself. However, the study was revealing to allow others to, at this point, following trails for the creation of knowledge that can solve the obvious flaws that we, as members of the information society, we do not come back to us also look at social individuals because its physical isolation (asylum) itself does not mean intellectual and information needs.